2017
DOI: 10.1002/chem.201704133
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polynuclear Aromatic Hydrocarbons using Ruthenium‐Ion‐Catalyzed Oxidation: The Role of Aromatic Ring Number in Reaction Kinetics and Product Distribution

Abstract: Oxidation of aromatic hydrocarbons with differing numbers of fused aromatic rings (2-5), have been studied in two solvent environments (monophasic and biphasic) using ruthenium-ion-catalyzed oxidation (RICO). RICO reduces the aromaticity of the polyaromatic core of the molecule in a controlled manner by selective oxidative ring opening. Moreover, the nature of the solvent system determines the product type and distribution, for molecules with more than two aromatic rings. Competitive oxidation between substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 33 publications
4
17
0
Order By: Relevance
“…The initial coordination of RuO 4 at the 9,10‐position is also consistent with the experimentally observed oxidation products previously reported in which oxidation was found to give diketones, dialdehydes or acids at these positions both in pyrene and phenanthrene . To see how this [3+2] complex may lead to the observed products, we have mapped out the reaction steps for oxidation of the PAHs starting with the [3+2] adduct in the 9,10‐positions using the same DFT approach.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The initial coordination of RuO 4 at the 9,10‐position is also consistent with the experimentally observed oxidation products previously reported in which oxidation was found to give diketones, dialdehydes or acids at these positions both in pyrene and phenanthrene . To see how this [3+2] complex may lead to the observed products, we have mapped out the reaction steps for oxidation of the PAHs starting with the [3+2] adduct in the 9,10‐positions using the same DFT approach.…”
Section: Resultssupporting
confidence: 82%
“…Analysis by 1 H NMR spectroscopy of the products from the pyrene oxidation reaction carried out in the monophasic solvent system showed two major products: pyrene‐4,5‐dione, 6 , and pyrene‐4,5‐dialdehyde, 4 , as expected from Scheme . Similarly, analysis of the oxidation product mixture when using phenanthrene, 1 , as substrate suggested that the main product in the monophasic solvent system is the dione (9,10‐phenanthrenequinone, 9 ) along with a trace amount of biphenyl‐2,2′‐dicarbaldehyde, 10 (Scheme S2, Supporting Information) . These products are consistent with the two primary products expected from the mechanism discussed in the DFT section above.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations